Primary structure of bovine vitamin K-dependent protein S. - Dahlbäck, B (1986)
Protein S is a vitamin K-dependent plasma protein that functions as a cofactor to activated protein C in the inactivation of coagulation factors Va and VIIIa. The nucleotide sequence of a full-length cDNA clone, obtained from a bovine liver library, was determined and the amino acid sequence was deduced. In addition, 95% of the structure was determined by protein sequencing. Protein S consists of 634 amino acids in a single polypeptide chain and has one asparagine-linked carbohydrate side chain. The cDNA sequence showed that the protein has a leader sequence, 41 amino acid residues long. The amino-terminal part of the molecule containing gamma-carboxyglutamic acid is followed by a region, residues 42-75, with two peptide bonds that are very sensitive to cleavage by thrombin. Residues 76-244 have four cysteinerich repeat sequences, each about 40 residues long, that are homologous to the precursor of mouse epidermal growth factor. In contrast to the other vitamin K-dependent plasma proteins, the carboxyl-terminal part of protein S is not homologous to the serine proteases.